The age of igneous and metamorphic events in the western Cape Breton Highlands, Nova Scotia - Jamieson, R. A.; Breemen, O. van; Sullivan, R. W.; Currie, K. L. (Canadian Journal of Earth Sciences, 1986)
Plutonic rocks of four different ages have been recognized in the Cape Breton Highlands on the basis of U–Pb dating of zircons. Two plutons, the North Branch Baddeck River leucotonalite [Formula: see text] and the Chéticamp pluton (550 ± 8 Ma), give dates that fall within the range of Late Proterozoic to Cambrian ages considered characteristic of the Avalon tectonostratigraphic zone of the eastern Appalachians. Late Ordovician to Silurian tonalite (Belle Côte Road orthogneiss, 433 ± 20 Ma) was metamorphosed, deformed, and incorporated into the central Highlands gneiss complex by approximately 370–395 Ma. High-level subvolcanic plutons (Salmon Pool pluton, [Formula: see text]) postdate all metamorphic rocks in the area. The presence of the older plutons is consistent with interpretation that the Cape Breton Highlands form part of the Avalon zone, but the presence of Ordovician–Silurian plutonic rocks and Devonian amphibolite-facies metamorphism is anomalous in comparison with the Avalon zone of Newfoundland and southeastern Cape Breton Island. Terranes with similar Late Proterozoic to mid-Paleozoic plutonic and metamorphic histories form a discontinuous belt along the northwest side of the Avalon zone southwest of Cape Breton Island. These rocks probably reflect events during and after the accretion of the Avalon zone to North America.